The demographic environment: Notes on eight economic, social and cultural threats - Matías Membiela-Pollán; Valentín Alejandro Martínez Fernández; Óscar Juanatey-Boga (Atlantic Review of Economics (ARoEc), 2018)
This article aims to highlight eight implications presented by the demographic environment in the economic, social and cultural fields. More specifically, we will deal with how the ageing of the population, evident in the advanced countries, infers a set of threats related to: 1) The sustainability of the social protection system, 2) The maintenance of public services, 3) The economic dynamism, 4) The subjective well-being, 5) The outcrop of "new brains", 6) The persistence of cultural identity, 7) The hustle and bustle of vibrant towns and villages, and 8) the strength of social capital and civil society. From the synthesis exposed, this article concludes that the scenario of strong demographic depression present in a large part of the developed countries, clearly harms their socio-economic and cultural sustainability.
Keywords: J10; 330; Demography; economic dynamism; public services; subjective well-being; cultural identity; social capital